Multiple arterial coronary bypass grafting is associated with greater survival in women. Issue 11 (20th October 2020) - Tam, Derrick Y; Rocha, Rodolfo V; Fang, Jiming; Ouzounian, Maral; Chikwe, Joanna; Lawton, Jennifer; Ko, Dennis T; Austin, Peter C; Gaudino, Mario; Fremes, Stephen E
Abstract : Objective: Multiple arterial grafting (MAG) in coronary artery bypass grafting (CABG) is associated with higher survival and freedom from major adverse cardiac and cerebrovascular events (MACCEs) in observational studies of mostly men. It is not known whether MAG is beneficial in women. Our objectives were to compare the long-term clinical outcomes of MAG versus single arterial grafting (SAG) in women undergoing CABG for multivessel disease. Methods: Clinical and administrative databases for Ontario, Canada, were linked to obtain all women with angiographic evidence of left main, triple or double vessel disease undergoing isolated non-emergent primary CABG from 2008 to 2019. 1:1 propensity score matching was performed. Late mortality and MACCE (composite of stroke, myocardial infarction, repeat revascularisation and death) were compared between the matched groups with a stratified log-rank test and Cox proportional-hazards model. Results: 2961 and 7954 women underwent CABG with MAG and SAG, respectively, for multivessel disease. Prior to propensity-score matching, compared with SAG, those who underwent MAG were younger (66.0 vs 68.9 years) and had less comorbidities. After propensity-score matching, in 2446 well-matched pairs, there was no significant difference in 30-day mortality (1.6% vs 1.8%, p=0.43) between MAG and SAG. Over a median and maximum follow-up of 5.0 and 11.0 years, respectively, MAG was associated with greater survival (HR 0.85, 95% CI 0.75 to 0.98) and freedom from MACCE (HR 0.85, 95% CI 0.76 to 0.95). Conclusions: MAG was associated with greater survival and freedom from MACCE and should be considered for women with good life expectancy requiring CABG.